2011
DOI: 10.1586/eog.11.28
|View full text |Cite
|
Sign up to set email alerts
|

Lack of evidence for prescription of antepartum bed rest

Abstract: Antepartum bed-rest treatment is based on assumptions that it is both effective and safe for mother and fetus. However, research indicates, that bed-rest treatment is ineffective for preventing preterm birth and fetal growth restriction, and for increasing gestational age at birth and infant birthweight. Studies of women treated with pregnancy bed-rest identify numerous side effects, including muscle atrophy, bone loss, weight loss, decreased infant birthweight in singleton gestations and gestational age at bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 58 publications
0
36
0
2
Order By: Relevance
“…Although clinical experience suggests that restricting physical exertion may help women at high risk of premature labor, or for women who are already in premature labor, there is no evidence that this actually lowers the rate of preterm birth (38). There has not been any randomized trial of bed rest in the prevention or treatment of premature labor in single pregnancy, and a trial of bed rest in twin pregnancies revealed no benefit (39).…”
Section: Bed Restmentioning
confidence: 99%
See 1 more Smart Citation
“…Although clinical experience suggests that restricting physical exertion may help women at high risk of premature labor, or for women who are already in premature labor, there is no evidence that this actually lowers the rate of preterm birth (38). There has not been any randomized trial of bed rest in the prevention or treatment of premature labor in single pregnancy, and a trial of bed rest in twin pregnancies revealed no benefit (39).…”
Section: Bed Restmentioning
confidence: 99%
“…There has not been any randomized trial of bed rest in the prevention or treatment of premature labor in single pregnancy, and a trial of bed rest in twin pregnancies revealed no benefit (39). The greater the degree of immobilization, the higher the risk of maternal complications such as thrombosis and muscle atrophy (38).…”
Section: Bed Restmentioning
confidence: 99%
“…Bed rest during pregnancy is sometimes prescribed to help prevent complications, but bed rest itself is associated with numerous physiological and psychosocial changes that alter the functions of every major organ system. 6 Several studies have reported that hospitalized women were significantly more depressed than women in other groups with whom they were compared. 7,8 With regard to the perception of risk, research findings suggest that if a woman perceives an above-average total risk to herself and her infant, she will experience increased levels of uncertainty, higher psychological distress and reduced well-being.…”
mentioning
confidence: 99%
“…Aerospace studies use the term bed rest to mean muscle disuse. Maloni JA [1] in her study defined antepartum bed rest as confinement to bed in hospital with activity limited to toileting. With this definition they observed that a pregnant woman spends about twenty-two hours in bed per day.…”
Section: Defining Bed Restmentioning
confidence: 99%
“…In the common parlance it is advised by some doctors, even in a normal setting. Antepartum bed rest is advised based on the assumption that it might be both effective and safe for the mother and the fetus [1]. On many occasions, it is prescribed without sound evidence to its utility and sometimes just to allow the benefit of doubt to the expectant mother.…”
Section: Introductionmentioning
confidence: 99%